Sheath-core polymer strand and method for producing same
The contact extension process addresses the challenges of existing core-sheath fiber production by enabling controlled release and structural integrity in polymer fibers, using a phase-separated interface to form core-sheath structures without harmful solvents.
Patent Information
- Application Number
- JP2024536527
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-01-11
- Filing Date
- 2023-01-09
- Publication Date
- 2025-01-24
AI Technical Summary
Existing methods for producing core-sheath polymer fibers, such as coaxial electrospinning and emulsion electrospinning, face challenges in controlling the interface characteristics and reproducibility, and often require high voltages and irritating solvents, which can damage functional compounds.
A method involving a contact extension process where a nucleating element is inserted through a first polymer composition, creating a phase-separated interface with a second polymer composition, allowing for the formation of core-sheath fibers with controlled release characteristics by differing functional additives in the core and sheath, without the need for emulsifiers or high-pressure mixing.
Enables the production of fibers with adjustable diameters and controlled release properties, eliminating the need for harmful solvents and enhancing the structural integrity and functionality of the fibers.
Smart Images

Figure 2025501896000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of U.S. Provisional Patent Application No. 63 / 298,255, filed January 11, 2022, the entire contents of which are incorporated herein by reference. FIELD OF THE DISCLOSURE This application relates to polymer strands and methods of making polymer strands, particularly polymer strands having a core and a sheath around the core. [Background technology]
[0002] Polymer microfibers and nanofibers, with their high surface-to-volume and strength-to-weight ratios, have a variety of applications and are used in the fabrication of conductive materials, protective clothing, fuel cell components, aerospace materials, filters, telecommunications components, drug delivery vehicles, tissue engineering scaffolds, smart textiles, and sensors. To impart additional functionality and thereby expand the potential applications of these polymer fibers, multicomponent systems such as sheath-core fibers have attracted significant attention. Perhaps the most widely recognized application of sheath-core fibers is the controlled release of compounds of interest localized in the core, sheath, or both compartments of the sheath-core fiber. The release of the compound encapsulated in the core can be controlled by varying the concentration and chemical composition of both the core and sheath of the fiber. Others have also developed sheath-core fibers with living cells encapsulated within the fiber core, which may have applications in tissue engineering and cell delivery.
[0003] Coaxial electrospinning and emulsion electrospinning are the two most common methods for core-sheath fiber production. In coaxial electrospinning, a dual capillary spinneret is used to feed two dissimilar materials so that a coaxial jet is formed. A high voltage is applied to the spinneret through which the solutions flow, forming a Taylor cone, and the electrostatic potential thins the polymer jet. The two components in coaxial electrospinning can be two spinnable polymer solutions, or one spinnable polymer solution as the sheath and one non-spinnable Newtonian fluid or powder as the core. Meanwhile, in emulsion electrospinning, two immiscible solutions can be spun simultaneously. In emulsion electrospinning, one polymer is usually dissolved in an organic solvent to form a continuous, easily spinnable phase, and the other polymer is dissolved in water to form the aqueous phase. The dispersed aqueous phase then becomes the core of the electrospun fiber, and the continuous phase becomes the sheath of the fiber. However, both coaxial and emulsion electrospinning can be difficult to control the interfacial and viscoelastic properties of the spinning solution, which can result in poorly structured fibers and poor reproducibility of specific polymer formulations.In addition, the electrospinning process involves high voltages and often uses harsh solvents to efficiently produce fibers, both of which can damage the encapsulated compounds that give the fibers their advanced functionality.
[0004] Emulsion electrospinning utilizes the phase separation between organic solvents and water stabilized by surfactants / emulsifiers. If electrospinning could be replaced by other methods such as dry spinning, needle spinning, touch spinning, track spinning, and contact drawing (a type of free surface spinning), it would also be possible to produce sheath-core fibers using water / water-polymer mixtures, also known as water-in-water two-phase systems (ATPS).
[0005] There is a need for methods of producing sheath / core fibers, particularly methods suitable for processing phase separated polymer solutions into fibers, and the sheath / core fibers obtained thereby. Summary of the Invention
[0006] A process for producing a core-sheath polymer strand includes inserting a nucleating element at least partially through a first laid composition into a second laid composition, the first laid composition comprising a first polymer and the second laid composition comprising a second polymer, drawing the nucleating element through the first laid composition and out of the second laid composition, and then continuing to draw the nucleating element out of the first laid composition such that a polymer strand comprising a core of the first polymer encapsulated in a sheath of the second polymer is drawn out of the laid composition by the nucleating element.
[0007] The core-sheath polymer strand comprises a core comprising a first polymer encapsulated in a sheath comprising a second polymer, the first polymer being crosslinked and having a first functional additive encapsulated therein, the second polymer being crosslinked and having a second functional additive encapsulated therein, the first functional additive being the same as the second functional additive but the first functional additive being encapsulated in the first polymer at a concentration different from the concentration of the second functional additive encapsulated in the second polymer, or the first functional additive being different from the second functional additive.
[0008] In this process, the first (core) polymer and the second (sheath) polymer can be crosslinked differently, so that the time release characteristics between the core and the sheath can be different. Thus, the functional additives added to the first and second pressed compositions and encapsulated in the core and the sheath can be released at different times, which is particularly useful for the controlled release of functional additives (e.g., pharma- ceutical active agents), especially two different additives.
[0009] The process for producing sheath-core polymer strands offers other important advantages over other core-shell technologies. For example, the process described herein provides control of strand diameter, allowing for the production of strands with diameters in the range of 1-100 microns. Standard coextrusion techniques result in core-shell strands with diameters of 100-200 microns. Electrospinning techniques produce strands with diameters of 100 nm or less. The process described herein allows for the realization of the intermediate scale of 1-100 microns, which is important for molecular interactions with functional additives. The process also eliminates the need for emulsifiers, high pressure mechanical mixing, or ultrasonic homogenization, which can affect the structure and function of compounds encapsulated in the strands. The process is versatile and easily scalable, providing a tunable approach to producing functional sheath-core polymer strands, which can be applied to many applications.
[0010] Additional features will be described or become apparent during the course of the following detailed description. It should be understood that each feature described herein can be utilized in any combination with any one or more of the other described features, and that each feature is not necessarily dependent on the presence of other features, unless otherwise apparent to one of ordinary skill in the art. For a clearer understanding, preferred embodiments will now be described in detail, by way of example only, with reference to the accompanying drawings, in which: [Brief description of the drawings]
[0011] [Figure 1] FIG. 1 shows a schematic diagram of a horizontal contact drawing system used to draw dextran-PEO core-sheath polymer strands from a liquid reservoir containing an aqueous two-phase system (ATPS) of dextran and polyethylene oxide (PEO). [Figure 2A]Graph of strand breakage (%) as a function of τpull(s) for a polymer solution containing 10 wt% PEO in water and 50 wt% dextran in water. Each data point is the breakage calculated from 20 trials, and each data set is fitted with a Weibull cumulative distribution function (shown as a dashed line). [Figure 2B] A graph of strand breakage (%) as a function of τpull(s) and fitted data curves using a Weibull cumulative distribution function for a core-sheath polymer solution containing 10 wt% PEO and 50 wt% dextran in water are shown. For reference, breakage plots for fibers formed from aqueous solutions of 10 wt% PEO or 50 wt% dextran are shown. [Diagram 3] The hydrodynamics of dextran-PEO during contact drawing are shown. (A) Mechanism of core-sheath strand generation from an immiscible aqueous solution of dextran and PEO, where dextran is located at the front of the reservoir and PEO at the rear of the reservoir. (B) A frame from a 60 frames / s video after the needle has been withdrawn shows the needle path into the PEO phase, the phase separation interface between the dextran and PEO phases, and the presence of cone-like structures in the dextran phase. (C) Movement of the microneedle through a reservoir containing dextran and PEO. Scale bars in (B) and (C) are approximately 500 μm. [Figure 4] The path of the microneedle through the reservoir (captured after withdrawal) is shown in the contact drawing process depicted in Figure 3. Deflection of the dextran-PEO interface is visible in the bulk PEO phase several minutes after microneedle withdrawal. [Figure 5A] Figure 4 shows an image of the spin cone formed by PEO as the PEO sheath is pulled from the PEO phase into the dextran phase during the contact stretching process of Figure 3. In the image, the direction of pulling is to the right of the image. [Figure 5B] 4 shows an image of a spin cone formed by dextran in the contact drawing process of FIG 3 as the dextran core is drawn out of the dextran phase into air. The drawing direction is to the right of the image. [Figure 6] Epifluorescence images of strands formed from the dextran-PEO interface. The localization of FITC-dextran and pyrene-PEG-rhodamine supports a core-sheath structure when the dextran solution is placed in front of the reservoir and the PEO solution in back of the reservoir (left panel). When the PEO solution is placed in front of the reservoir and the dextran solution in back of the reservoir, thin strands of discontinuous FITC-dextran and pyrene-PEG-rhodamine signals are formed (right panel). [Figure 7] PEO-dextran hydrodynamics during contact drawing, with the dextran solution placed behind the reservoir and the PEO solution placed in front of the reservoir. (A) Mechanism of strand formation. (B) A frame from a 60 frames per second video after microneedle withdrawal showing the expected microneedle path into the dextran phase, the phase separation interface between the dextran and PEO phases, and the presence of cone-like structures in the PEO phase. (C) Movement of the microneedle through a reservoir containing PEO and dextran. Scale bars in (B) and (C) are approximately 500 μm. [Figure 8] 8 is an image showing the localization of the dextran and PEO phases after microneedle withdrawal in the contact drawing process of FIG. 7. [Figure 9] Hydrodynamics of a spin cone extending from the fluid surface in a reservoir for the process in Figure 3. (A) Representative image and (B) associated radius decay plot of a spin cone formed from 50 wt% dextran. (C) Representative image and (D) radius decay plot of a spin cone formed from 10 wt% PEO. (E) Representative image and (F) radius decay plot of a spin cone formed from an ATPS of 50 wt% dextran and 10 wt% PEO. Time t=0 is defined as the time when the needle begins to move out of the polymer reservoir. In all cases, the pulling length is 100 mm and the pulling speed is 400 mm / s. R is the final radius and R0 is the initial radius. [Figure 10]Attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectra of strands formed from PEO, dextran, and dextran-PEO ATPS at (A) 2% pressure and (B) 30% pressure. [Figure 11] The core diameter is shown to be proportional to the dextran concentration. (A) Representative optical sections by confocal microscopy from 10 wt% PEO (tracked with pyrene-PEG-rhodamine) and either 52 wt% dextran or 60 wt% dextran (tracked with FITC-dextran). Scale bar is 50 μm. (B) Core diameter of 100 mm long core-sheath strands with varying dextran concentration. Data points are mean ± standard deviation and were fitted with a second order polynomial function. [Figure 12] Optical images of strands formed from either two dextran solutions or two PEO solutions of different concentrations and viscosities. Scale bar is 50 μm. [Figure 13] Microscopic images of PEO strands crosslinked by UVC irradiation at intensities of 400 mJ / cm2 or 0 mJ / cm2 in the presence of 25 wt%, 10 wt%, or 5 wt% PEGDA containing 2 wt% Irgacure® 2959 as a photoinitiator before and 1 h after hydration in PBS buffer. Scale bar is 10 μm. [Figure 14] Shown are microscopic images of dextran strands crosslinked by irradiation with UVC radiation at an intensity of 400 mJ / cm2 or 0 mJ / cm2 in the presence of 10 wt%, 5 wt% or 2.5 wt% photodextran (PhDex) containing 2 wt% Irgacure® 2959 as a photoinitiator before hydration with PBS buffer and 1 hour after hydration with PBS buffer. Scale bar is 10 μm. [Figure 15]Micrographs of PEO and dextran strands crosslinked by irradiation with UVC radiation at an intensity of 400 mJ / cm2 or 0 mJ / cm2 in the presence of 0 wt% PEGDA and 0 wt% photodextran without Irgacure® 2959 as a photoinitiator, before hydration in PBS buffer and 1 hour after hydration in PBS buffer. Scale bar is 10 μm. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The process includes first inserting a nucleating element through a first prepared lay composition comprising a first polymer. While the nucleating element passes through the first prepared lay composition, the first polymer adheres to the nucleating element. When the nucleating element protrudes into the second prepared lay composition, the first polymer remains attached to the nucleating element. In a preferred embodiment, the first prepared lay composition is immiscible in the second prepared lay composition, and the first prepared lay composition is in contact with the second prepared lay composition at a phase separation interface. In a preferred embodiment, the nucleating element does not penetrate the phase separation interface when protruding into the second prepared lay composition, but instead deflects the phase separation interface into the second prepared lay composition.
[0013] The nucleating element is then withdrawn from the second laid composition. As the nucleating element is withdrawn from the second laid composition, the phase separation interface is no longer deflected. As the end of the nucleating element passes from the second laid composition to the first laid composition through the initial location of the phase separation interface, a negative pressure is created that deflects the phase separation interface into the first laid composition, causing the phase separation interface to locally rupture and the second polymer is drawn into and through the first laid composition. As the nucleating element continues to be withdrawn from the first laid composition, a liquid bridge is created at the interface between the first laid composition and the external environment (e.g., air). As the nucleating element continues to be withdrawn, the polymer strand is withdrawn from the liquid bridge. The polymer strand thus produced comprises a core of the first polymer encapsulated in a sheath of the second polymer. The second polymer is initially pulled through the first pressed transverse composition as a thin-walled cone by rupture of the phase separation interface, but the cone is a transient structure that disappears once a liquid bridge is formed at the interface between the first pressed transverse composition and the external environment.
[0014] The first prepared lay composition is preferably immiscible in the second prepared lay composition, providing a phase separation interface between the two prepared lay compositions when they are in contact with each other. The surface tension between the first and second prepared lay compositions at the phase separation interface helps to reduce the diffusion of components between the prepared lay compositions. The second prepared lay composition preferably has a higher zero shear viscosity than the first prepared lay composition, allowing the transient cone of the second prepared lay composition to persist within the first prepared lay composition while the liquid bridge is established. If a less viscous prepared lay composition is used as the second prepared lay composition (i.e., "backwards"), the second prepared lay composition may cause premature relaxation that leads to strand failure. The negative pressure generated is different from the positive pressure used in other core-shell processes such as coextrusion. In positive pressure processes, the more viscous phase forms the core of the strand, whereas in the process disclosed herein, the more viscous phase can form the sheath. It is therefore surprising that the "near" laid lay composition can form the core of the strand, while the farther laid lay composition can form the sheath of the strand. Thus, in a preferred embodiment, the nucleating elements are inserted through the less viscous laid lay composition before being inserted into the more viscous laid lay composition, and the nucleating elements are withdrawn from the less viscous laid lay composition after being withdrawn from the more viscous laid lay composition.
[0015] The first and second pressed compositions each include a first and a second polymer. The first and second polymers may be the same or different, but are preferably different polymers. When the first and second polymers are different, the first polymer may be immiscible in the second polymer, so that the first pressed composition is immiscible in the second pressed composition. The first and second polymers are any polymers that can independently form polymer strands when drawn from the pressed composition by a nucleating element. Examples of polymers include polysaccharides, polypeptides, polynucleotides, polyolefins, polyvinyls, polystyrenes, polyacrylonitriles, polyacrylics, polyamides, polyesters, polycarbonates, polysulfones, polyimides, polyethylene oxides, polyketones, fluoropolymers, polysilicones, and the like, as well as crosslinked polymers and copolymers thereof.
[0016] Specific examples of polymers include alginic acid, amylopectin, bovine serum albumin, carrageenan, carboxymethylcellulose, carboxymethyldextran, casein, chitosan, chondroitin sulfate, collagen (e.g., type I collagen), dextran, dextran sulfate, diethylaminoethyldextran, fetal bovine serum, gelatin, guar gum, gum arabic, gum ghatti, hyaluronic acid, hydroxyethylcellulose, hydroxyethylstarch, hydroxypropylcellulose, hydroxypropylmethylcellulose, lignin, methylcellulose, mucin, pectin, peptone, poloxamer 407, poly(2-acrylamido-2-methyl-1-propanediol), ... propanesulfonic acid), poly(2-ethyl-2-oxazoline), polyethylene oxide, poly(4-styrenesulfonic acid), poly(4-styrenesulfonic acid-co-maleic acid), poly[bis(2-chloroethyl)ether-alt-1,3-bis[3-(dimethylamino)propyl]urea] quaternized, poly-(α,β)-DL-aspartic acid, poly-D-lysine, poly(acrylamide), poly(acrylic acid), poly(allylamine), poly(diallyldimethylammonium chloride), poly(ethylene glycol), poly(ethylene glycol) diacrylate, poly(ethyleneimine), poly(methacrylic acid), poly(methyl vinyl ether-alt-maleic acid), Poly(N-isopropylacrylamide), poly(propylene glycol), poly(sucrose), poly(vinyl alcohol), poly(vinylpyrrolidone), poly(vinyl sulfonic acid), polyoxyethylene(9) nonylphenyl ether, polyoxyethylene(20) sorbitan monolaurate, polyoxyethylene(23) lauryl ether, pullulan, silk (e.g., spider silk, Bombyx mori silk, other insect silks), tragacanth, and xanthan gum.
[0017] The pressed strand composition may include additional components such as respective liquid media, respective crosslinking agents, respective functional additives, or other components useful in strand formation.
[0018] The first laid composition preferably comprises a first liquid medium in which a first polymer is dispersed. The second laid composition preferably comprises a second liquid medium in which a second polymer is dispersed. The first and second liquid media may be the same or different. When the liquid media are the same, the immiscibility of the first and second polymers may impart the immiscibility of the first and second laid compositions. However, when the first and second polymers are the same or miscible with each other (i.e., non-phase separated polymers), the immiscibility of the first and second liquid media is used to impart the immiscibility between the first and second laid compositions, such that a phase separation interface is formed where the first and second laid compositions are in contact.
[0019] By utilizing mutually immiscible polymers and mutually immiscible liquid media, phase separation between the first and second prepared lay compositions can be further promoted, providing a more clearly defined phase separation interface between the two prepared lay compositions when they are in contact with each other. A physical barrier between the first and second prepared lay compositions can also be utilized, along with a means for allowing nucleating elements to pass in and out of the first and second prepared lay compositions.
[0020] For each of the first and second pressed strand compositions, the liquid medium is suitable for dispersing the polymer therein when in use. Preferably, the liquid medium is a solvent capable of dissolving the polymer. The liquid medium may be an aqueous medium, an organic medium, or a mixture thereof. Aqueous media include, for example, pure water, buffer, saline, other salt solutions, and other aqueous solutions. Organic media may include organic solvents, for example, aliphatic solvents (e.g., pentane, hexane, chloroform, dichloromethane, etc.), aromatic solvents (e.g., toluene, aniline, etc.), alcohols, ethyl, ketones, organic sulfoxides, or mixtures thereof. Aqueous media are particularly important when producing core-sheath strands for use in pharmaceutical applications, such as, for example, controlled release of a pharma- ceutical active agent or precursor thereof. In some embodiments, the first and second liquid media are both aqueous media.
[0021] To enhance the structural integrity, stability and dissolution resistance of the core and / or sheath, the first and / or second polymers may be crosslinked polymers before the strands are formed, when the core-sheath polymer strands are formed, or after the strands are formed. In some embodiments, the process includes crosslinking the first polymer, the second polymer, or both the first and second polymers before the strands are formed, when the strands are formed, or after the strands are formed. Crosslinking can be accomplished in a number of ways, including including a chemical crosslinking agent in the first laid composition, the second laid composition, or both the first and second laid compositions. Alternatively or additionally, the crosslinking agent may be electromagnetic radiation, such as ultraviolet (UV) light, alone or together with an initiator (e.g., a photoinitiator such as benzophenone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propan-1-one, etc.). The nature of the crosslinking agent will depend in part on the nature of the polymer being crosslinked, the desired level of structural integrity of the core and sheath, and the end use of the core-sheath strand.
[0022] Some examples of chemical crosslinkers include 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC), aldehydes (e.g., glyoxal, formaldehyde, glutaraldehyde), acrylates (e.g., polyethylene glycol diacrylate (PEGDA), photodextran (i.e., methacrylated dextran), etc.), free radical generating crosslinkers (e.g., peroxides, e.g., 2,5-bis(tert-butylperoxy)-2,5-dimethylhexane), ionic crosslinkers, disulfides, amino acid diamines (e.g., lysine, lysine methyl ester, and cystine dimethyl ester), borax to provide crosslinks via hydrogen bonds, other reversible crosslinkers, thermosetting to provide physical crosslinks (e.g., gelatin, agarose, Matrigel™, etc.), or combinations thereof.
[0023] In some embodiments, the first polymer is crosslinked to a different extent than the second polymer, providing differential crosslinking of the core and sheath. Differential crosslinking of the core and sheath strands to provide differential control of the structural integrity, stability, and dissolution resistance of the core and sheath is particularly useful for producing controlled time release materials in which the timing is tailored for a specific purpose. Differential crosslinking allows the core (first polymer) and sheath (second polymer) to be crosslinked to different degrees, thereby tailoring the relative time to dissolution of the core and sheath in a specific environment (e.g., an aqueous environment in the body). The difference in dissolution time of the core and sheath can be used to differentially control the timing of release of the functional additive in the core and the functional additive in the sheath. This is particularly useful in timed drug release applications. In some embodiments, the first and second pressed strand compositions may each contain a chemical crosslinker, which is activated after strand formation. By controlling the concentration of the crosslinker in each pressed strand composition, different degrees of crosslinking can be achieved in the core and sheath, which is useful for controlling the timed release of the functional additive entrained in the core and sheath.
[0024] Any of a number of strategies can be employed to obtain differential crosslinking between the core and the sheath. For example, a crosslinking agent can be added to the first and / or second laid compositions, and the concentration of the crosslinking agent in each laid composition is controlled to provide the desired level of crosslinking. Additionally, click chemistry can be used as a fast reaction with a one-step reaction for crosslinking. In another strategy, polyethylene glycol-acrylate (PEG-acrylate) or other acrylated polymers can be used as the scaffold polymer, and the degree of substitution of the PEG-acrylate can be controlled. In another strategy, the core-sheath strands can be formed in air with an active crosslinking agent for the sheath in the gas phase, which allows crosslinking of the sheath only. Additionally, the pH and / or temperature of the first and second laid compositions may be differentially controlled to provide differential crosslinking. Additionally, when radiation (e.g., UV light) is used in crosslinking, the sheath can be made from a laid composition that includes an opaque material so that the radiation used for crosslinking does not penetrate to the core. Also, when radiation is used for crosslinking, photosensitizers and / or quenchers can be selectively utilized in the laid composition to control the degree of crosslinking. When ionic crosslinking is used, differential core and sheath crosslinking can be achieved by adding a chelating agent to one or both of the pressed lay compositions.
[0025] One or both of the first and second laid compositions may include one or more functional additives. The first laid composition may include one or more first functional additives. The second laid composition may include one or more second functional additives. The one or more functional additives may be any chemical or physical entity or combination of chemical and / or physical entities for a desired purpose. In this way, the one or more functional additives are incorporated into the core or sheath of the core-sheath strand, depending on which laid composition includes the functional additive. The surface tension between the immiscible first and second laid compositions at the phase separation interface, the difference in the affinity of the functional additives for the first and second laid compositions, and the partitioning to the interface all help to reduce the diffusion of the functional additives between the laid compositions. This is important when creating a core-sheath geometry with different functional additives and / or different concentrations of functional additives in the core and sheath, allowing for dual controlled release applications. Thus, it is possible to simultaneously incorporate different functional additives into the core and sheath of the strand during the formation of the strand. It is also possible to simultaneously incorporate functional additives in the core and sheath of the strands while they are being formed, at the same or different concentrations.
[0026] The core-sheath strands produced by this process, especially those with different crosslinking between the core and the sheath, are advantageously useful in controlled or time-release materials, whereby one or more functional additives can be released in a controllable or timed manner over time as the sheath dissolves to release a second functional additive contained therein, and then the core dissolves to release a first functional additive contained therein. In embodiments where the first and second functional additives are the same chemical or physical entity, the core-sheath strands can be used to controllably release different concentrations of functional additives over time. Thus, both the core and the sheath can function as time-release vehicles for the respective functional additives, and the time-release characteristics between the core and the sheath can be distinct.
[0027] Examples of functional additives include sugars, growth factors, hormones, extracellular matrix proteins (ECM) (e.g., collagen (e.g., type I collagen), fibronectin, laminin, etc.), enzymes, cytokines, chemokines, antibodies (e.g., monoclonal antibodies, etc.), anti-inflammatory agents, steroids, immunosuppressants, chemotherapeutic agents, lipids, hyaluronic acid, liposomes, micro / nanocapsules, genetic material (DNA (e.g., plasmids), RNA (e.g., mRNA, interfering RNA, etc.)), extracellular vesicles, whole cells, metal ions, Non-metallic ions, nanoparticles (carbon nanotubes, metal nanoparticles, etc.), solid particulates (metal, plastic, glass, etc.), colorants, surfactants, detergents, vitamins, bases, mineral acids, organic acids (citric acid, etc.), other natural health ingredients (citric acid, etc.), other natural health products, other small molecule pharmaceuticals (e.g., minocycline, riluzole, dalfampridine, escitalopram, deoxygedunin, 7,8-dihydroxyflavone, quercetin, dexamethasone, tacrolimus) and combinations thereof. The functional additive is preferably a pharma- ceutical active agent, a precursor of a pharma- ceutical active agent, or a combination thereof, particularly one that is soluble in an aqueous medium.
[0028] The speed at which the nucleation elements are pulled can affect the length and thickness of the polymer strands produced in the process. Preferably, the nucleation elements are pulled at a rate that is proportional to the pull time (τ rep ) is the first reptation time (τ rep 1), thereby inducing a viscoelastic response in the first pressed lay composition as the polymer strand is pulled by the nucleating element. pull ) also represents the second reptation time (τ rep 2), thereby inducing a viscoelastic response in the second pressed strand composition as the polymer strands are pulled by the nucleating elements.
[0029] The reptation time (τ) of the polymer in the pressed resin composition rep ) is the time required to relax the entanglement of the polymer chains in the pressed composition. The reptation time is preferably as long as possible to increase the pull time, but not greater than the desired pull time. The reptation time is preferably at least 0.01 seconds, more preferably at least 1 second. The reptation time is preferably in the range of 1 second to 1,000 seconds. In some embodiments, the reptation time is in the range of 1 second to 100 seconds. In other embodiments, the reptation time is in the range of 1 second to 10 seconds.
[0030] The pull time (τ) of nucleating elements from pressed compositions pull ) is τ pull The pull time (τ) is defined as the path length / pulling speed, where the path length is the set distance over which the nucleation element pulls the polymer strand, and the pulling speed is the rate at which the nucleation element pulls the strand over the set distance. pull ) can alternatively be defined in terms of the strand instead of the nucleating element, where the pull time (τ pull ) is τ pull = strand length / pull rate, where strand length is the set length over which the polymer strand is pulled, and pull rate is the rate at which the strand is pulled over that length. The pull time of a strand (τ pull ) is the τ of the nucleation element when the strand is connected to the nucleation element pull It is the same as l. τ in relation to the strand pull Defining β is useful when the strands are transferred from the nucleation element to a strand take-up mechanism, which is preferred in a continuous strand formation process.
[0031] In this process, the pull time of the nucleation element (or the strand, if the strand is not connected to a nucleation element) is preferably equal to or shorter than the reptation time (τ rep The reptation time of the polymer (τ rep A pull time shorter than the reptation time induces a viscoelastic response in the pressed lay composition as the strands of polymer are pulled from the pressed lay composition. Thus, at pull times shorter than the reptation time, the entanglements act as temporary crosslinks, resulting in a viscoelastic response, which allows the polymer strands to be pulled from the pressed lay composition without breaking. However, if the interaction time of the nucleating elements or already formed strands with the entangled polymer in the pressed lay composition is longer than the reptation time, the entanglements are abandoned and the strands break. Preferably, the pull time is selected to maximize the length of the strands at the desired pull speed. The pull speed is preferably in the range of 0.1-4 m / s, or 0.5-4 m / s, or 0.5-3 m / s, or 0.5-2 m / s.
[0032] In addition, the concentration of the polymer in each of the laid compositions can affect strand formation. Preferably, the first polymer has a concentration in the first laid composition that is less than the first overlap concentration (c * The concentration of the first polymer in the first laid composition is more preferably equal to or greater than the first entanglement concentration (c e 2) or more. Preferably, the second polymer has a concentration in the second laid composition that is greater than or equal to the second entanglement concentration (c * The concentration of the second polymer in the second laid composition is more preferably equal to or greater than the second entanglement concentration (c e 1) That's all.
[0033] The overlap concentration of the polymer in the pressed composition (c * ) is the minimum concentration of polymer in the pressed run composition at which the conformations of individual polymer chains begin to overlap with each other. This is the point at which the concentration in a given infiltration volume is equal to the concentration of polymer in the pressed run composition. The polymer concentration in the pressed run is equal to or greater than the overlap concentration.
[0034] The entanglement concentration of the polymer in the pressed composition (c e ) is the concentration of polymer in the laid lay composition at which individual polymer chains begin to entangle with each other. The entanglement concentration is always at least as great as the overlap concentration, but can be up to 1000 times greater than the overlap concentration. In many cases, the entanglement concentration is at least 10 times greater than the overlap concentration. Preferably, the concentration of polymer in the laid lay composition is equal to or greater than the entanglement concentration. Preferably, the concentration of polymer in the laid lay composition is high enough that the entire laid lay composition is in the entanglement region.
[0035] The concentration of the polymer in the press-formed composition is preferably at least 0.01% by weight, more preferably in the range of 0.01% to 99% by weight, based on the total weight of the press-formed composition. The required concentration of the polymer depends on the molecular weight (M W ) depending in part on the molecular weight of the polymer. Generally, lower concentrations are required for polymers with higher molecular weights. Preferably, the polymer has a molecular weight (M) of 1 kDa or more, or 5 kDa or more, or 10 kDa or more, or 35 kDa or more, or 40 kDa or more, or 50 kDa or more, or 70 kDa or more, or 100 kDa or more, or 1,000 kDa or more, or 8,000 kDa or more. W In some embodiments, the polymer has a molecular weight (M) of 20,000 kDa or less. W ).
[0036] The withdrawal rate of the nucleating element and the concentration of the polymer in the pressed lay composition are further discussed in International Patent Application PCT / CA2021 / 051110, filed August 12, 2021, the entire contents of which are incorporated herein by reference.
[0037] The bulk viscosity of the pressed lay composition can be adjusted to control the strand diameter, since a low bulk viscosity results in thin strands. A high bulk viscosity of the pressed lay composition can form thicker strands. However, if the viscosity of the pressed lay composition is too low, the spin cone collapses and destroys the growing strands, and if the viscosity is too high, the negative pressure induced by the moving nucleating elements is not sufficient to allow the formation of strands. Therefore, it is important to properly set the viscosity of the pressed lay composition. In some embodiments, the bulk viscosity of the pressed lay composition is preferably in the range of 8-100 Pa·s (8,000 cP-100,000 cP) as measured by the vertical falling ball method. In another embodiment, the bulk viscosity of the pressed composition is preferably in the range of 100-5,000 Pa·s (100,000-5,000,000 cp), more preferably 100-1,000 Pa·s (100,000-1,000,000 cp), even more preferably 100-400 Pa·s, even more preferably 150-300 Pa·s, even more preferably 175-250 Pa·s, for example 200 Pa·s, as measured with a StressTech™ HR rheometer.
[0038] The bulk viscosity of the prepared lay composition is influenced by the concentration of the polymer in the prepared lay composition. Increasing the concentration of the polymer in the prepared lay composition increases the bulk viscosity, while decreasing the concentration decreases the bulk viscosity. Thus, the diameter of the strands produced can be adjusted by adjusting the concentration of the polymer in the prepared lay composition. The diameter of the strands produced can also be adjusted by controlling the withdrawal speed of the nucleating element, whereby a higher speed results in a smaller diameter strand. The withdrawal speed of the nucleating element is preferably in the range of 0.1-4 m / s, or 0.5-4 m / s, or 0.5-3 m / s, or 0.5-2 m / s. By appropriately adjusting the viscosity of the prepared lay composition and the withdrawal speed of the nucleating element, an average strand diameter in the range of 200,000-1,000,000 nm can be achieved.
[0039] The nucleation element can be any object at which strands can nucleate when the element is inserted into the prepared composition. Strand nucleation causes a portion of the prepared composition to adhere to one or more nucleation sites on the nucleation element, for example in the form of a droplet. When the nucleation element is pulled away from the prepared composition, a liquid bridge is formed between the prepared composition on the nucleation element and the prepared composition remaining in the reservoir, and when the nucleation element is further pulled away from the reservoir, a polymer strand is formed between the nucleation element and the reservoir. The nucleation element provides non-random nucleation of the polymer. With non-random nucleation, one or more nucleation sites can be predetermined to better control strand growth and other process steps. The nucleation element has a size and shape such that the polymer forms a strand when the nucleation element is pulled away from the prepared composition. The aspect ratio (height to maximum width) of the nucleation element is preferably in the range of 1:100 to 1000:1. In some embodiments, the aspect ratio preferably ranges from 1:1 to 1000:1. The nucleation elements preferably have a cap width small enough to allow the thin polymer strands to initially adhere thereto when the cap is inserted into the pressed lay composition. The width of the nucleation element to which the polymer strands adhere is preferably 0.5-4 mm, more preferably 2-4 mm. In some embodiments, the width of the nucleation element may be 1 mm or less, or 0.75 mm or less, for example 0.5 mm. The cap preferably has a flat, conical, pyramidal, or elliptical shape.
[0040] The nucleation element has a surface, and the nucleation element preferably has a surface area of at least 11 mm 2 , preferably at least 50 mm 2 The pressed layer is inserted into the pressed layer so that the pressed layer is wetted by each pressed layer over a surface area of up to 400 mm. Preferably, the wetted surface area is up to 400 mm. 2 , more preferably up to 200 mm 2 , and more preferably up to 110 mm 2and preferably has a wetted surface area of 11-400 mm 2 , more preferably 11-200mm 2 , and more preferably 11-110 mm 2 , more preferably 50-110mm 2 , more preferably 60-90mm 2 The range is.
[0041] A single nucleation element can be used to draw one polymer strand. However, multiple strands can be drawn simultaneously from the same pressed strand composition by using multiple discrete nucleation elements. Multiple nucleation elements may be provided in an array with regular or random spacing, either in a regular or irregular arrangement. When multiple nucleation elements are used, the multiple nucleation elements preferably have a minimum center-to-center spacing between nucleation elements that is at least 1.5 times, preferably at least 2 times, more preferably at least 2.5 times the diameter of the thickest adjacent nucleation element. In some embodiments, the spacing is at least 0.2 mm, preferably at least 0.5 mm, more preferably at least 1 mm. The lower limit is primarily due to the resolution of the 3D printer and the tolerances that can be achieved by machining. The thickness of the desired strands will affect the minimum spacing as well as the width of the nucleation elements. Thicker strands may require larger pin spacing and / or wider nucleation elements. The nucleation elements can be manufactured by any suitable method, such as 3D printing or machining. The nucleation elements can have any suitable shape, for example, polygonal or elliptical in cross section. Some examples of nucleation elements include pins, needles, rods, and surface projections (e.g., posts, ridges, nodules, granules, etc.). In some embodiments, one or more types of such nucleation elements are attached to multiple bases and used to pull multiple strands simultaneously. Thus, pin brushes and the like can be used to pull multiple strands simultaneously.
[0042] The nucleation element may be embodied in a device that includes features for mounting or fixing the nucleation element, containing the prepared strand composition, and translating the nucleation element into and out of the prepared strand composition. During strand formation, the nucleation element may be oriented in any direction, for example, horizontally or vertically. In some embodiments, the prepared strand composition is contained in a reservoir in which the first and second prepared strand compositions are arranged vertically one on top of the other or horizontally side-by-side. Other mounting and containing arrangements may be envisioned by those skilled in the art. Features for translating the nucleation element may include a motorized or manually driven stage. Automated devices are preferred.
[0043] After strand nucleation on the nucleation element, the strand can be transferred from the nucleation element to a strand take-up mechanism (e.g., a continuous spinning device such as a godet) that can continuously draw and collect the strand. In this manner, strands of indefinite length can be produced. [Example]
[0044] Referring to FIG. 1, by way of example, free surface spinning of core-sheath polymer strands is illustrated using a simple horizontal contact drawing system 1 consisting of a motorized linear stage 2, a microneedle 3 attached to the stage 2, and a liquid reservoir 4 containing an aqueous two-phase system (ATPS) consisting of two immiscible aqueous polymer solutions 5, 6. The two immiscible polymer solutions (phases) exemplified here are an aqueous solution of dextran 5 (dextran phase) and an aqueous solution of polyethylene oxide (PEO) 6 (PEO phase). The aqueous polymer solutions 5, 6 are arranged side-by-side in the reservoir 4 with a phase separation interface 7 between the aqueous polymer solutions 5, 6 where the aqueous polymer solutions 5, 6 are in contact with each other. Because the interfacial tension between PEO and dextran is lower than that of an oil / water system, the present approach can eliminate the need for emulsifiers and high pressure mechanical mixing or ultrasonic homogenizers, any of which may affect the structure and function of compounds that may be encapsulated in the resulting polymer strands. Stage 1 is configured to move linearly or in a linear fashion such that microneedle 3 can be inserted into reservoir 4 and removed from reservoir 4 along a linear path at a constant speed over a constant distance. System 1 is arranged such that when microneedle 3 is inserted into reservoir 4, it first encounters dextran phase 5 before encountering PEO phase 6. Similarly, when microneedle 3 is retracted from reservoir 4, it exits dextran phase 5 through dextran / air interface 8 into the external environment (air). Details of contact stretching are provided below. EXAMPLES
[0045] Preparation of dextran-PEO core-sheath strands Materials and Methods
[0046] Polymer Solutions PEO (1 MDa; Sigma-Aldrich) and dextran (500 kDa; Dextran Products Ltd.) were dissolved in deionized water to obtain a solution of 10-15 wt% PEO and 50-60 wt% dextran. The polymer solution was vortex mixed for 10 min and then bath sonicated until a homogenous solution was formed. Once the polymer was dissolved, the solution was stored at room temperature or in the refrigerator (approximately 4 °C).
[0047] Fluorescein isothiocyanate (FITC)-labeled dextran (500 kDa; Sigma-Aldrich) and pyrene-polyethylene glycol (PEG)-rhodamine or mPEG-FITC (both 10 kDa; Creative PEGWorks) were dissolved in the dextran solution and PEO solution at 0.1 wt %, respectively, to perform fluorescence imaging of the polymer solution and the core-sheath fibers.
[0048] contact stretching A B9 Creator® microstereolithography 3D printer using B9R-2 Black Resin (B9 Creations) was used to create rectangular reservoirs measuring 2 × 5 × 5 mm with open surfaces on the top and front (see Chowdhry G, et al. Polymer entanglement drives formation of fibers from stable liquid bridges of highly viscous dextran solutions, Soft Matter. 17(7), 1873-1880 (2021)), the entire contents of which are incorporated herein by reference. The reservoirs were used to hold viscous polymer solutions for contact stretching using steel microneedles with a tip diameter of 0.1 mm and a shank diameter of 0.5 mm (Ted Pella, Inc.; product number 13601C). For fiber formation / breakage analysis of individual PEO and dextran solutions, approximately 50 μL of liquid was added to the reservoirs using a syringe. In all other experiments, approximately equal volumes of PEO and dextran solutions were added to the reservoirs, with one of the polymer solutions at the rear of the reservoir and the other at the front of the reservoir, such that the interface between the polymer solutions was perpendicular to the bottom of the reservoir and the path of the microneedle.
[0049] The steel microneedle was mounted on a linear translation stage (Thorlabs; DDSM100 / M). The stage was programmed to move at a speed of 30 mm / s to a depth of approximately 5 mm so that the tip of the microneedle entered the reservoir. At this depth, the microneedle paused for 0.5 s and then moved at a controlled speed (V pull ) and returned to the original position. The acceleration was 5000mm / s 2 The maximum speed was about 400 mm / s. pull The failure rate was calculated as follows:
[0050] [ka] Starting from 0% damage, V is measured until 100% damage is observed. pull was reduced.
[0051] An imaging system consisting of a Mightex® 5 megapixel CMOS camera, a long working distance lens assembly, and a 150 watt halogen light source (Fiber-Lite® Mi-150 Illuminator Series) was used to video record the strand formation process near the reservoir at a rate of 60 frames / s. These images were later processed using the threshold utility in MATLAB® to understand the thinning profile of the liquid bridge. An in-house MATLAB® script was used to calculate the diameter of the liquid bridge several millimeters away from the base of the spin cone by tracking the position of the edge of the dark spin cone against the light background.
[0052] To observe the fluid dynamics of the dextran and PEO solutions in the reservoir, another glass reservoir of similar dimensions to the 3D-printed reservoir was fabricated by gluing two 25 × 25 mm glass cover slips together with a ~2 mm high bead of hot glue, resulting in a single-use transparent reservoir in which the movements of the microneedle, dextran phase, and PEO phase could be recorded using either the Mightex® camera setup described above or a Yinama® portable digital microscope with integrated color camera.
[0053] Fluorescence microscopy A Nikon Eclipse Ti optical microscope equipped with 10x and 20x long working distance objectives was used for routine inspection of the FITC-dextran and pyrene-PEG-rhodamine-containing fibers and for recording fluorescent images of the PEO and dextran phases in the transparent reservoir after needle withdrawal. For detailed inspection of the strand morphology and confirmation of the formation of core-sheath strands, the strands were observed using a Leica SP8 close-up super-resolution laser scanning confocal microscope equipped with a 20x air objective (NA 0.75, WD 0.21 mm). For presentation, the fluorescent images were processed with Image J and adjusted for brightness, contrast, and color balance. Quantification of the core diameter was performed in MATLAB.
[0054] Attenuated Total Reflectance Fourier Transform Infrared Spectroscopy (ATR FTIR) A Thermo Scientific Nicolet® iZ10 MX integrated FTIR microscope was used to collect the infrared spectra of the fibers. This instrument is capable of recording infrared spectra and analyzes microscopic fibers with a minimum aperture of 25 μm × 25 μm. The mapping function was performed in ATR mode using a liquid nitrogen cooled conical germanium crystal and a slide-on ATR objective with an MCT detector. The contact pressure between the crystal and the strand was varied and spectra were collected for strands formed only from dextran and PEO (2% pressure) and for strands formed from core-sheath fibers (30% pressure). Spectra were collected from 400-4000 cm -1 The data consisted of 16 scans taken between 100 and 1500 m, with a spectral resolution of 4 cm. -1 Prior to data collection, atmospheric suppression was performed to correct absorbance for CO2 and humidity. Data collection and post-processing of spectra were performed using OMNIC PICTA® software.
[0055] Results and Discussion Free surface spinning of contact-spun strands from a single polymer solution is driven by polymer entanglements. The reptation model for polymer entanglements predicts characteristic time scales for polymer chain motion above which the chains can move freely relative to each other, and below which the chains form entanglements at the contact points with nearby chains. At slower pulling rates, corresponding to longer time scales, the probability of strand formation from an entangled polymer solution decreases. The ability to form strands from various polymer formulations (shown in Figures 2A and 2B) can be understood by analyzing the breakage rates according to the Weibull cumulative distribution function, i.e.,
[0056] [ka] where k is a shape parameter that represents the width of the distribution, and a is a scale parameter that corresponds to the time when the failure rate reaches 63%.
[0057] Damage analysis Strand formation begins with the formation of a liquid bridge between the surface of a viscous polymer solution and the tip of the microneedle. When the contacting substrate is removed from the liquid surface, the liquid in the liquid bridge is drawn into the strand by elongational flow, which results in the strand rapidly drying in air as it elongates. The formation of the liquid bridge depends on the viscosity of the fluid and its tendency to form entanglements on the time scale of the microneedle moving through the fluid. In a failure analysis of the polymer solution, as seen in Figure 2A, the formation of a liquid bridge depends on the viscosity of the fluid and its tendency to form entanglements on the time scale of the microneedle moving through the fluid.
[0058] As can be seen in Figure 2A, the Weibull distribution has a longer τ pull The 50 wt% solution of dextran formed strands more efficiently than the 10 wt% solution of PEO, as can be seen by the shift in the τ value. As can be seen in Figure 2B, for the core-sheath strands, the results were relatively similar to PEO and dextran alone, with a τ pullThe damage rate was 0% for durations of up to 1.5 seconds, but pull 100% breakage was not achieved until τ was significantly higher at 20 s. A comparison of breakage distribution curves for dextran, PEO, and dextran / PEO sheath-core is shown in Figure 2B. Strand formation efficiency was lowest for 10 wt% PEO, slightly better for 50 wt% dextran, and best for sheath-core strands. This indicates that τ pull As the value increases, the rate of breakage decreases, as indicated by a rightward shift in the curve (Figure 2B). For example, τ pull For values between 2 and 4 seconds, the breakage rate of the sheath-core strands was between 5% and 20%, whereas for values between τ pull At a value of 4 seconds, the failure rates of the individual polymers were between 65% and 80%.
[0059] The failure analysis helps to evaluate the formation of liquid bridges between the polymer solution and the microneedle, and thus the formation of strands. When pulled, the liquid bridges form strands by elongational flow, which dries quickly as the strands elongate. Overall, the sheath-core strands were able to withstand slower pull-out speeds while maintaining a lower breakage rate. Thus, sheath-core strands are suitable for producing strands at lower pulling speeds. Since sheath-core strands can be pulled at slower pulling speeds while maintaining a lower breakage rate compared to single polymer strands, the sheath-core strands are more suitable for scale-up and can be utilized in more applications. Furthermore, the intermediate region of pulling speeds, i.e., τ pull At values in the range of 2 seconds to 4 seconds, the sheath-core strands appear noticeably stiffer, stronger, and thicker.
[0060] Observation of real-time video of the contact drawing process reveals the behavior of viscous stock solutions of dextran and PEO. Consistent with other reports of the viscoelastic behavior of dextran of various molecular weights and concentrations, the 50 wt% dextran solution behaved as a Newtonian fluid, but some studies have observed gradual shear-thinning behavior at 30 wt% or higher molecular weight dextran, which is attributed to the presence of branching within the dextran chains. In contrast, PEO behaved as a non-Newtonian fluid above concentrations sufficient for entanglement to occur, consistent with previous reports on the rheology of aqueous PEO solutions. While in aqueous dextran solutions the time scale for strand formation was controlled purely by entanglement dynamics, the PEO results suggest that the time scale for strand formation from aqueous PEO solutions is controlled by entanglement dynamics and a thinning process that depends on the shear strain rate.
[0061] Hydrodynamics of liquid bridge formation from dextran / PEO solutions. With an understanding of the critical time scales for the formation of polymer strands from individual solutions of dextran and PEO, we investigated the ability to form strands from an ATPS formed from these polymer solutions. One of the polymer solutions was placed behind the reservoir and the other in front of the reservoir. Figure 3A shows the mechanism by which strands form from an ATPS in which the dextran solution is placed in front of the reservoir and the PEO solution in the rear of the reservoir. The microneedle first moves through the dextran solution, and as the microneedle enters the PEO phase, it deflects the phase separation interface rather than penetrating it. As the microneedle is withdrawn, negative pressure is created, drawing a thin-walled cone of PEO through the dextran phase (Figure 3A middle, Figure 3B, and Figure 5A). The path of the microneedle through the PEO phase is revealed by bright-field imaging and by fluorescent imaging of FITC-dextran incorporated in the dextran phase (Figure 4). However, the cone of PEO in the dextran phase is a transient structure that disappears once a liquid bridge forms at the dextran–air interface. This is evident from the absence of pyrene-PEG-rhodamine signal in the dextran phase less than a minute after the microneedle is withdrawn. The cone of dextran in air as the core-sheath strand forms is shown in Figure 5B. If strand formation is successful, a strand containing FITC-dextran and pyrene-PEG-rhodamine signals is observed by epifluorescence imaging (see Figure 6, left panel). The time course for such events is shown in Figure 3C, showing the movement of the microneedle relative to the air-dextran-PEO interface.
[0062] With the dextran solution at the back of the reservoir and the PEO solution at the front of the reservoir, the negative pressure created by this microneedle withdrawal results in a thin-walled cone of dextran passing through the PEO phase (see Figures 7 and 8). A few minutes after microneedle withdrawal through the PEO phase, the path of the microneedle through the dextran became apparent, with a partially collapsed cone of dextran present in the PEO phase, and signs of instability and collapse of the thin-walled dextran column present in the PEO phase close to the air-PEO interface (Figure 7). The strands formed in this configuration were significantly thinner than those formed in the configuration where the dextran was at the front of the reservoir. Furthermore, the presence of signal from FITC-dextran and pyrene-PEG-rhodamine was discontinuous along the length of the strand in epifluorescence images (see Figure 6, right panel). These data indicate that the complex flow patterns occurring within the reservoir are carried by liquid bridges and the resulting strands, and suggest that the core-sheath structure exists only when the PEO solution is drawn as a thin liquid sheath through the dextran phase.
[0063] Differences in the morphology and dynamics of spin cones formed from dextran, PEO, and ATPS formed from dextran and PEO were also evident (see Figure 9). In solutions of 50 wt% dextran, the spin cones were either symmetric or oblique depending on their proximity to the side of the reservoir (Figure 9A), and the radius decreased linearly over time (Figure 9B). For 10 wt% PEO solutions, the cone volume was smaller than the cone formed from 50 wt% dextran (Figure 9C), and after an initial phase of rapid exponential decay, the radius decayed exponentially at a slower rate, as expected for the thinning of polymer liquid bridges in the elastocapillary region (Figure 9D). Spin cones generated from ATPS formed from 50 wt% dextran and 10 wt% PEO had smaller volumes than spin cones formed from dextran, but larger volumes than spin cones formed from PEO (Figure 9E). The radius of the spin cones generated from ATPS, after an initial phase of rapid exponential decay, exponentially decayed at a rate similar to that of the PEO spin cones (Figure 9F). This radius decay behavior is likely due to the relative differences in the viscoelastic properties of the two polymers. Visual observation of the process confirmed that fluid from the PEO phase enters the cone only under shear, with a secondary flow within the cone back to the reservoir. For dextran, it was previously observed that the strand diameter increases with increasing dextran concentration, which is likely due to the larger volume of fluid present in the spin cones of various dextran formulations compared to those formed from PEO.
[0064] Changes in core diameter with dextran concentration The presence of a sheath-core structure in the strands formed from ATPS was verified by ATR FTIR (see Figure 10). At low pressure (2% pressure) between the germanium crystal and the fiber, the FTIR spectra of the PEO and sheath-core fibers appear identical, with a peak at 1100 cm -1A prominent narrow dextran peak near the surface of the core-sheath fiber is not detected (Figure 10A). Since light penetrates 0.66 μm in this condition, the thickness of the PEO sheath may be greater than 0.66 μm. Increasing the pressure of the pure two fibers to 30% does not change the FTIR spectrum of the dextran fiber, but the peak at 800-1200 cm -1 The PEO peak in the region changes (Figure 10B). Increasing the pressure of the core-sheath fiber to 30% changes the peak in the region from 800 to 1200 cm. -1 Along with the PEO peak in the region of 1100 cm -1 A mixed spectrum is formed with a nearby dextran peak (Figure 9B).
[0065] The presence of a core-sheath structure in the strands formed from ATPS was conclusively confirmed by confocal microscopy, which also allowed the analysis of strands varying in core diameter as a function of dextran concentration (see Figure 11). Tuning of the core diameter was possible by varying the weight percentage of dextran added to the reservoir from which the strands were drawn. As the dextran concentration was increased from 50 to 60 wt%, the core diameter increased. However, the thickness of the PEO sheath did not increase with increasing dextran concentration. This suggests that the dextran loading is the primary determinant of the core-sheath strand diameter and that the PEO sheath thins along the length of the strand as it is stretched by the contact stretching device. Finally, the ability to form core-sheath structures was examined when a 60 wt% dextran solution containing FITC-labeled dextran was placed on the front of the reservoir and a 50 wt% unlabeled dextran solution was placed on the back of the reservoir, and when a 14 wt% PEO solution containing FITC-labeled PEO was placed on the front of the reservoir and a 10 wt% PEO solution containing pyrene-PEG-rhodamine was placed on the back of the reservoir (see FIG. 12). When the 60 wt% dextran solution was placed on the front of the reservoir and the 50 wt% dextran solution on the back of the reservoir, the resulting strands had a thin outer sheath formed from the 60 wt% dextran solution, a thick inner sheath formed from the 50 wt% dextran solution, and a core formed from the 60 wt% solution. When 14 wt% PEO was placed on the front of the reservoir and 10 wt% PEO was placed on the back of the reservoir, thin strands were formed and no core-sheath structure was observed. These data suggest that ATPS is favorable for the formation of core-sheath structures by free surface spinning.
[0066] Example 1 shows a relatively simple, nozzle-free approach to generate sheath-core strands from an ATPS formed from dextran and PEO. Free surface spinning of the sheath-core strands after contact-drawing liquid bridge formation can be scaled up by moving from a single-pin apparatus to a multi-pin array. EXAMPLES
[0067] Crosslinking of PEO and dextran strands Materials and Methods Polymer Solutions For crosslinking of PEO, polyethylene glycol diacrylate (PEGDA) (4000DA, Polysciences) crosslinker and Irgacure® 2959 (Sigma-Aldrich, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one) photoinitiator were used. Irgacure® 2959 has an absorption peak at 365 nm. Aqueous solutions of 10 wt% PEO and 25 wt% PEGDA, 10 wt% PEGDA, 5 wt% PEGDA and 0 wt% PEGDA were prepared similarly to the solutions prepared in Example 1. The prepared solutions were either treated with 2 wt% Irgacure® 2959 before contact drawing or used without photoinitiator.
[0068] For the crosslinked dextran, photodextran (Advanced Biomatrix), a methacrylated dextran with a MW of 35-50 kDa, was used. Solutions of 40 wt% dextran and 10 wt% photodextran, 50 wt% dextran and 5 wt% photodextran, 50 wt% dextran and 2.5 wt% photodextran, and 50 wt% dextran and 0 wt% photodextran were prepared in the same manner as the solutions prepared in Example 1. The prepared solutions were either treated with 2 wt% Irgacure® 2959 before contact drawing or used without the addition of a photopolymerization initiator.
[0069] Prior to pulling polymer strands from the prepared PEO and PEGDA polymer solutions or the prepared dextran and photodextran polymer solutions, Irgacure® 2959 was added. Prior to adding Irgacure® 2959 to the polymer solutions, Irgacure® 2959 was dissolved in dimethyl sulfoxide (DMSO) at a concentration of 100 mg / mL. A vortex was used to homogenize the photoinitiator and the appropriate amount of photoinitiator was added to each polymer solution. The polymer solutions with freshly added photoinitiators were stored wrapped in tin foil.
[0070] Contact stretching was carried out in the same manner as in Example 1.
[0071] UVC crosslinking of polymer strands To crosslink the polymer strands, a UVP crosslinker CL-3000 purchased from analytikjena was used. The polymer strands were crosslinked at 400 mJ / cm 2 and 0 mJ / cm 2 The strands were then treated with UVC (without UVC). The glass microscope slides with the pulled strands were placed in the apparatus and exposed to the desired amount of UVC. After UVC treatment, the polymer strands were stored in the dark.
[0072] Hydration of crosslinked polymer strands Hydration with 2mL of 1X PBS was used to measure the level of crosslinking that occurred within each strand sample. A scalpel was used to gently cut the strands surrounding the coverslip on the glass slide. Using a cyanoacrylate adhesive, four small drops of adhesive were placed on each corner of the bottom of the coverslip, which was then placed into one well of a 6-well plate. Four small drops of adhesive were also placed on top of the strands at the four corners of the coverslip slide to help keep the strands in place. Each well of the 6-well plate was similarly filled with the other samples. The plate was then wrapped in tin foil to keep the fibers in the dark. 2mL of 1X PBS was added to each well plate to hydrate the fibers.
[0073] Microscopic imaging To qualitatively monitor the level of cross-linking that had occurred in the polymer fibers, micrographs were taken of the fibers before hydration and after 1 h of hydration.
[0074] <Results and Discussion> Figure 13 shows microscopy images of PEO polymer strands UVC crosslinked in the presence of 25 wt%, 10 wt%, and 5 wt% PEGDA using 2 wt% Irgacure® 2959 as a photoinitiator before hydration (contact stretching) and 1 hour after hydration with PBS. Samples were exposed to 400 mJ / cm 2 or 0 mJ / cm 2 The cross-linked strands appeared more transparent and clear after hydration compared to before hydration. At a low PEGDA concentration of 5 wt%, the fibers were more transparent after hydration compared to fibers formed in the presence of 25 wt% and 10 wt% PEGDA, suggesting that the less cross-linked PEO fibers are also less stable in aqueous media.
[0075] Figure 14 shows microscopy images of UVC crosslinked dextran fibers in the presence of 10 wt%, 5 wt%, and 2.5 wt% photodextran and 2 wt% Irgacure® 2959 before hydration (contact stretching) and 1 hour after hydration with PBS. The same UVC irradiation conditions as above were used. Similar to the crosslinked PEO strands, the crosslinked dextran strands appear more transparent and clear after hydration compared to before hydration. At low photodextran concentrations (5 wt% and below), the fibers became more transparent after hydration compared to fibers formed in the presence of 10 wt% photodextran, and in some cases the fibers completely dissolved, suggesting that the less crosslinked dextran fibers are also less stable in aqueous media.
[0076] Furthermore, UVC irradiation level, photoinitiator concentration, and crosslinker concentration did not significantly affect the shape or uniformity of the crosslinked PEO strands before and after hydration, which was unexpected. Since PEO and dextran are hydrophilic and should dissolve upon hydration, it was believed that crosslinking would occur and that a crosslinker was necessary to solve the solubility problem. Further testing of PEO strands exposed to UVC light in the absence of both PEGDA, photodextran, and Irgacure® 2959 showed that after 1 hour of hydration, the strands completely lost their shape and dissolved (Figure 16), supporting the idea that Irgacure® 2959 and crosslinkers (PEGDA and photodextran) are necessary to produce stable fibers in aqueous media.
[0077] The relative humidity of the atmosphere was recorded before contact drawing. PEO strands with all concentrations of PEGDA and 2 wt% Irgacure® 2959, as well as PEO strands crosslinked without Irgacure® 2959, were drawn at 50%-60% relative humidity (Figures 13 and 15). Dextran strands crosslinked in the presence of 2.5 wt% photodextran were pulled at 40% relative humidity, dextran strands crosslinked in the presence of 5 wt% photodextran were pulled at 20% or less relative humidity, and dextran strands crosslinked in the presence of 10 wt% photodextran were pulled at 50% relative humidity (Figure 14). Dextran strands exposed to UVC without the presence of photodextran and photoinitiator were pulled at 50% relative humidity (Figure 15). EXAMPLES
[0078] Preparation of cross-linked dextran-PEO core-sheath strands Preparation of cross-linked dextran-PEO core-sheath strands
[0079] To produce sheath-core dextran-PEO strands with crosslinked core and / or sheath, a crosslinker for PEO (e.g., 2,5-bis(tert-butylperoxy)-2,5-dimethylhexane, PEGDA, etc.) is added to the PEO phase in the reservoir and / or a crosslinker for dextran (lysine, photodextran, etc.) is added to the dextran phase in the reservoir. Crosslinking is initiated, for example, by UV irradiation with or without a photoinitiator, and the sheath-core strands are drawn off to yield sheath-core polymer strands with either or both the core and sheath crosslinked. EXAMPLES
[0080] Fabrication of dextran-PEO core-sheath strands using functional additives To produce core-sheath dextran-PEO strands with functional additives loaded in both the core and sheath, the process described in Example 3 is carried out, except that a functional additive (antibody or nucleotide or polynucleotide) is also added to the PEO phase in the reservoir, and a functional additive (antibody or nucleotide or polynucleotide) is also added to the dextran phase in the reservoir.
[0081] The novel features will be apparent to those skilled in the art upon review of this specification. However, it should be understood that the scope of the claims should not be limited by the embodiments, but should be given the broadest interpretation consistent with the language of the claims and the entire specification.
Claims
1. 1. A method for producing a sheath-core polymer strand, comprising the steps of: inserting a nucleating element at least partially through a first prepared composition into a second prepared composition, said first prepared composition comprising a first polymer and said second prepared composition comprising a second polymer; drawing a nucleating element from said second pressed composition through said first pressed composition; and then continuing to draw the nucleating element from the first laid composition such that a polymer strand comprising a core of the first polymer encapsulated in a sheath of the second polymer is drawn from the laid composition by the nucleating element.
2. the first prepared composition is immiscible in the second prepared composition; the first pressed composition is in contact with the second pressed composition at a phase-separation interface; The method of claim 1 , wherein the second pressed composition has a higher zero shear viscosity than the first pressed composition.
3. The nucleating element has a pull time (τ pull ) speed, i.e. The first reptation time (τ) required to relax the entanglement of the polymer in the first pressed composition rep 1) is less than The second reptation time (τ ) required to relax the entanglements of the polymer in the second pressed composition rep 2) is less than 3. The method of claim 1 or 2, whereby a viscoelastic response is induced in the pressed strand composition when the polymer strands are stretched by the nucleating elements.
4. The first polymer may be selected from the group consisting of alginic acid, amylopectin, bovine serum albumin, carrageenan, carboxymethylcellulose, carboxymethyldextran, casein, chitosan, chondroitin sulfate, collagen, dextran, dextran sulfate, diethylaminoethyldextran, fetal bovine serum, gelatin, guar gum, gum arabic, gum ghatti, hyaluronic acid, hydroxyethylcellulose, hydroxyethylstarch, hydroxypropylcellulose, hydroxypropylmethylcellulose, lignin, methylcellulose, mucin, pectin, peptone, poloxamer 407, poly(2-acrylamido-2-methyl-1-propanesulfonic acid), poly(2-ethyl-2-oxazoline), polyethylene oxide, poly(4-styrenesulfonic acid), poly(4-styrenesulfonic acid-co-maleic acid), poly[bis(2-chloroethyl)ether-alt-1,3-bis 4. The process according to any one of claims 1 to 3, wherein the polyoxyethylene (9) nonylphenyl ether, polyoxyethylene (20) sorbitan monolaurate, polyoxyethylene (23) lauryl ether, pullulan, silk, tragacanth or xanthan gum is selected from the group consisting of quaternized [3-(dimethylamino)propyl]urea, poly-(α,β)-DL-aspartic acid, poly-D-lysine, poly(acrylamide), poly(acrylic acid), poly(allylamine), poly(diallyldimethylammonium chloride), poly(ethylene glycol), poly(ethylene glycol) diacrylate, poly(ethyleneimine), poly(methacrylic acid), poly(methyl vinyl ether-altomaleic acid), poly(N-isopropylacrylamide), poly(propylene glycol), poly(sucrose), poly(vinyl alcohol), poly(vinylpyrrolidone), poly(vinyl sulfonic acid), polyoxyethylene (9) nonylphenyl ether, polyoxyethylene (20) sorbitan monolaurate, polyoxyethylene (23) lauryl ether, pullulan, silk, tragacanth or xanthan gum.
5. the second polymer is selected from the group consisting of alginic acid, amylopectin, bovine serum albumin, carrageenan, carboxymethylcellulose, carboxymethyldextran, casein, chitosan, chondroitin sulfate, collagen, dextran, dextran sulfate, diethylaminoethyldextran, fetal bovine serum, gelatin, guar gum, gum arabic, gum ghatti, hyaluronic acid, hydroxyethylcellulose, hydroxyethylstarch, hydroxypropylcellulose, hydroxypropylmethylcellulose, lignin, methylcellulose, mucin, pectin, peptone, poloxamer 407, poly(2-acrylamido-2-methyl-1-propanesulfonic acid), poly(2-ethyl-2-oxazoline), polyethylene oxide, poly(4-styrenesulfonic acid), poly(4-styrenesulfonic acid-co-maleic acid); 5. The process according to any one of claims 1 to 4, wherein the polyoxyethylene (9) nonylphenyl ether, polyoxyethylene (20) sorbitan monolaurate, polyoxyethylene (23) lauryl ether, pullulan, silk, tragacanth or xanthan gum is selected from the group consisting of poly[bis(2-chloroethyl)ether-alt-1,3-bis[3-(dimethylamino)propyl]urea] quaternized, poly-(α,β)-DL-aspartic acid, poly-D-lysine, poly(acrylamide), poly(acrylic acid), poly(allylamine), poly(diallyldimethylammonium chloride), poly(ethylene glycol), poly(ethylene glycol) diacrylate, poly(ethyleneimine), poly(methacrylic acid), poly(methyl vinyl ether-alt maleic acid), poly(N-isopropylacrylamide), poly(propylene glycol), poly(sucrose), poly(vinyl alcohol), poly(vinylpyrrolidone), poly(vinyl sulfonic acid), polyoxyethylene (9) nonylphenyl ether, polyoxyethylene (20) sorbitan monolaurate, polyoxyethylene (23) lauryl ether, pullulan, silk, tragacanth or xanthan gum.
6. The method of any one of claims 1 to 5, wherein the first polymer and the second polymer are different polymers.
7. The process of claim 6 , wherein the first and second polymers are immiscible with each other.
8. 8. The method of claim 1, wherein the first pressed composition comprises a first polymer dispersed in a first liquid medium and the second pressed composition comprises a second polymer dispersed in a second liquid medium.
9. 9. The method of claim 8, wherein the first liquid medium is a first solvent that dissolves the first polymer and the second liquid medium is a second solvent that dissolves the second polymer, or the first liquid medium is a first solvent that dissolves the first polymer and the second liquid medium is a second solvent that dissolves the second polymer.
10. 10. The process of claim 8 or claim 9, wherein the first and second liquid media are both aqueous media.
11. 11. The method of any one of claims 1 to 10, further comprising crosslinking the first polymer, the second polymer, or both the first and second polymers before the strands are formed, as the strands are formed, or after the strands are formed.
12. The method of claim 11 , wherein the first polymer is crosslinked to a different extent than the second polymer.
13. The method according to any one of claims 1 to 12, wherein the first prepared lay composition comprises one or more first functional additives, and the second prepared lay composition comprises one or more second functional additives, or the first prepared lay composition comprises one or more first functional additives, and the second prepared lay composition comprises one or more second functional additives.
14. The method of claim 13, wherein the functional additive comprises one or more pharma- ceutical active agents, precursors of one or more pharma- ceutical active agents, or a combination thereof.
15. A sheath-core polymer strand comprising a core comprising a first polymer encapsulated in a sheath comprising a second polymer, the first polymer is crosslinked; A sheath-core polymer strand in which the second polymer is crosslinked.
16. 16. The sheath / core polymer strand of claim 15, wherein the first polymer encapsulates the functional additive or the second polymer encapsulates the functional additive.
17. the first polymer having a first functional additive contained therein and the second polymer containing a second functional additive; 16. The sheath-core polymer strand of claim 15, wherein the first functional additive is different from the second functional additive, or the first functional additive is the same as the second functional additive, but the first functional additive is included in the first polymer at a concentration different from the concentration of the second functional additive included in the second polymer.
18. 18. A polymer strand according to any one of claims 15 to 17, produced by a process according to any one of claims 1 to 14.